Revision of Xiphentedon Risbec, 1957 and Colpixys Waterston, 1916 (Hymenoptera, Eulophidae), with descriptions of new species from the Afrotropics - Gumovsky, Alex (European Journal of Taxonomy, 2023)
The genera Colpixys and Xiphentedon are revised. Both genera are of Afrotropical distribution and are very similar to Entedon, but distinguished by a median strip or furrow on the propodeum replacing the median carina of Entedon. The genus Xiphentedon is characterized by the complete lateral propodeal sulci delimiting convex submedian areas, prosternum with a flange, axillula with indentate projection, and densely hairy central mesopectus. The subgenus Cederholmia Gumovsky, 1997 of Entedon is considered a junior synonym of Xiphentedon, so two of its species are moved to the genus as X. halli (Gumovsky, 1997) comb. nov. and X. danielssoni (Gumovsky, 1997) comb. nov. The genus Colpixys is characterized by the lack of characters of Xiphentedon, but also by the broadly sculptured propodeum with the deep median furrow delimited laterally by two sinuous margins. Three (one new) species are recognized in Colpixys and sixteen (thirteen new) species allocated to three groups (kayovei, danielssoni and forceps), are assigned to Xiphentedon. The new species are: Colpixys eburnus sp. nov. from Ivory Coast and the Republic of South Africa (RSA), Xiphentedon neserorum sp. nov. from RSA, X. simoni sp. nov. from Tanzania, X. dewittei sp. nov. and X. musimba sp. nov. from the Democratic Republic of the Congo (DRC), X. jeanyvesi sp. nov. from Tanzania, the Central African Republic (CAR) and RSA, X. wieringai sp. nov. from Gabon and Ivory Coast, X. kivuensis sp. nov. from DRC, X. palabora sp. nov. from RSA, X. sangha sp. nov. from CAR, X. nimba sp. nov. from Guinea, X. forceps sp. nov. from Ivory Coast, Benin and RSA, X. gerardi sp. nov. from Benin, DRC and RSA, and X. acutigena sp. nov. from Ivory Coast, DRC, Tanzania and RSA. Morphological peculiarities and possible relationships of Colpixys, Xiphentedon, Entedon and some other genera, are discussed.